Letter (copy) : International Solidarity Fund - Help for Children of Spain - Tewson, Vincent
1938-11-08 038-0114-002 -2- and food, and the Standing Joint Committee of Industrial Women's Organisations which is working in close association with the International Solidarity Fund is supplying wool to Women's Sections, Women's Guilds, etc. for the knitting of garments for the Spanish children. Up to the moment 50,000 garments have been sent to Spain. I think that with these facts before them your Association will appreciate that the International Solidarity Fund is giving real assistance to the Spanish children and, should they decide to send a donation, I can assure them that it will be very welcome and will be used to the best possible advantage. Cheques should be made payable to the National Council of Labour and sent to this address when an official receipt will be sent by return. With many thanks for your interest in this matter, I am, Yours sincerely, Assistant Secretary. 292/946/38/114(II)